(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
Idioms, proverbs, similes and pantun all fall under the category of "metaphor" in Malay. Interestingly, the metaphors are not superficial; instead, they are permeated with philosophy, which in turn convey Malay thought. Clearly, these metaphors are composed using specific objects that have a close connection with meaning. Therefore, it is worthwhile to examine this connection and the meaning that is meant to be conveyed. This study focuses on data concerning idioms about mata[eyes] and kuku [fingernails]. References to ulam-ulaman (herbal plants eaten raw) were chosen for analysis of pantun. All of the data was taken from www.malaycivilization.com. The data analysis was performed using inquisitive semantics in an effort to uncover cognitive philosophical and cultural roles to explain why a particular object is selected for a particular metaphor. The actual meaning is revealed through three steps: literal, cognitive and inquisitive. The findings of this study show that the objects mata and kuku, as well as herbal plants, are aptly used to suggest the meaning that they are to convey. Mata signals feelings, kuku concerns closeness and herbal plants are associated with love, as proven by the data selected. The discussionthen extends to other fields, medicine and nutrition, in reference to proverbs and pantun. Clearly, this kind of multidisciplinary study is able to discuss Malay metaphors scientifically and convincingly. Keywords: object, metaphor, pantun, Malay mind, philosophy, culture